2005
DOI: 10.1364/jon.4.000586
|View full text |Cite
|
Sign up to set email alerts
|

Shannon capacities and error-correction codes for optical atmospheric turbulent channels

Abstract: The propagation of an ON-OFF keying modulated optical signal through an optical atmospheric turbulent channel is considered. The intensity fluctuations of the signal observed at the receiver are modeled using a gamma-gamma distribution. The capacity of this channel is determined for a wide range of turbulence conditions. For a zero inner scale, the capacity decreases monotonically as the turbulence strengthens. For non-zero inner scale, the capacity is not monotonic with turbulence strength. Two error-correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 29 publications
0
67
0
Order By: Relevance
“…The ergodic [11] and outage capacities [12] for a Poisson noise model and a Gaussian noise model [13] have been derived in the absence of misalignment errors. The performance of detection techniques [14], bounds on the pairwise error probability for a variety of coding schemes [15], [16], and low-complexity codes [11] have been considered for FSO channels. However, code rate design and joint optimization with the beam width for a finite detector aperture and pointing jitter has not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…The ergodic [11] and outage capacities [12] for a Poisson noise model and a Gaussian noise model [13] have been derived in the absence of misalignment errors. The performance of detection techniques [14], bounds on the pairwise error probability for a variety of coding schemes [15], [16], and low-complexity codes [11] have been considered for FSO channels. However, code rate design and joint optimization with the beam width for a finite detector aperture and pointing jitter has not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Esener et al [9] have reported extensive studies using hybrid onedimensional arrays of devices to demonstrate free-space optical interconnect on printed circuit boards for computer interconnects [9][10][11]. Previous efforts have mainly focused on understanding the core issues of atmospheric turbulence, beam misalignment, and error corrections [8,12,13], while very minimal work was done on developing the low-cost advanced detector arrays for high-speed FOS links.…”
Section: Introductionmentioning
confidence: 99%
“…Coding gains of RS and convolutional codes are sufficient under the regime of weak turbulence and in the absence of fog. However, in the presence of strong turbulence or deep fog, coding gains of RS or convolutional codes are insufficient, as shown in [10], and more advanced FEC schemes, such as turbo [8] or low-density parity-check (LDPC) codes [10], are needed.…”
mentioning
confidence: 99%
“…In this letter, we propose a power efficient coded-modulation scheme based on multilevel coding (MLC) [9] with LDPC codes [10] as component codes, suitable for the use in repetition MIMO FSO systems with -ary PPM. The proposed coded modulation scheme allows aggregation of RF/microwave signals and a conversion to the optical domain in a very natural way and may be a good candidate for hybrid RF/microwave-FSO systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation